Translocation of the Na(+)/H(+) exchanger 1 (NHE1) in cardiomyocyte responses to insulin and energy-status signalling - Lawrence, Scott P. (Portland Press Ltd., 2010)
The Na(+)/H(+) exchanger NHE1 is a highly regulated membrane protein that is required for pH homoeostasis in cardiomyocytes. The activation of NHE1 leads to proton extrusion, which is essential for counteracting cellular acidity that occurs following increased metabolic activity or ischaemia. The activation of NHE1 intrinsic catalytic activity has been well characterized and established experimentally. However, we have examined in the present study whether a net translocation of NHE1 to the sarcolemma of cardiomyocytes may also be involved in the activation process. We have determined the distribution of NHE1 by means of immunofluorescence microscopy and cell-surface biotinylation. We have discovered changes in the distribution of NHE1 that occur when cardiomyocytes are stimulated with insulin that are PI3K (phosphoinositide 3-kinase)-dependent. Translocation of NHE1 also occurs when cardiomyocytes are challenged by hypoxia, or inhibition of mitochondrial oxidative metabolism or electrically induced contraction, but these responses occur through a PI3K-independent process. As the proposed additional level of control of NHE1 through translocation was unexpected, we have compared this process with the well-established translocation of the glucose transporter GLUT4. In immunofluorescence microscopy comparisons, the translocation of NHE1 and GLUT4 to the sarcolemma that occur in response to insulin appear to be very similar. However, in basal unstimulated cells the two proteins are mainly located, with the exception of some co-localization in the perinuclear region, in distinct subcellular compartments. We propose that the mechanisms of translocation of NHE1 and GLUT4 are linked such that they provide spatially and temporally co-ordinated responses to cardiac challenges that necessitate re-adjustments in glucose transport, glucose metabolism and cell pH.